Routledge handbook of sports performance analysis - McGarry, Tim; O'Donoghue, Peter; Sampaio, António Jaime de Eira (Routledge, Taylor & Francis Group, 2013)
Sport performance analysis techniques help coaches, athletes and sport scientists develop an objective understanding of actual sport performance, as opposed to self-report, fitness tests or laboratory based experiments. This is a comprehensive guide to this exciting and dynamic branch of sport science.